A medicação crónica no período perioperatório: perfil de utilização e gestão de risco. - Liliana Castanheira; Ana Palmeiro; Paula Fresco; Ana Filipa Macedo (Acta Médica Portuguesa, 2012)
Currently, an increasing number of surgeries are performed in an older and higher risk population, due to the inherent comorbidity and polypharmacy associated with this population group. The characterization of drug usage profiles in the perioperative period is critically needed to understand the nature of adverse events and to achieve a more efficient iatrogenic risk management.During 1 year, all adult patients (>18 years) consecutively admitted for elective surgery at "Cova da Beira" Hospital Center (CHCB) were included in the study. The demographic characteristics, and data on chronic medication use and their administration to the patients in study, in the perioperative period were collected.A total of 404 patients were evaluated. The majority of patients (69.9%) were taking chronic medication (mean 2.5 by admission), mainly "anti-hypertensive" (58.5%) and "psychotropics" (33.5%). 973 drugs were registered as chronic medication. 79.1% of these drugs were withdrawn before the surgery, 10.7% were continued and 7.7% were replaced for another drug of the same therapeutic group.The majority of patients, admitted for general surgery, take chronic medications, which were withdrawn before surgery, in the majority of cases. Additional assessment of perioperative complications, as result of drug withdrawal, is urgently needed for surgical therapeutic management.